Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery
By depositing nanosilicon on the porous carbon matrix and forming a conductive polymer layer to form a silicon-carbon negative electrode material, the problem of poor cycle stability caused by volume expansion of the silicon-based negative electrode material in lithium-ion batteries is solved, and higher cycle stability and energy density are achieved.
Patent Information
- Application Number
- CN202411616479.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-18
AI Technical Summary
The silicon-based anode material expands severely during charging and discharging of lithium-ion batteries, resulting in poor circulation stability. The first time the Coulomb efficiency is low and the capacity attenuation is fast, limiting its commercial application.
Using a porous carbon matrix as the supporting material, nanosilicon is deposited on its surface through vapor deposition technology, and a conductive polymer layer is formed in situ on the surface of the nanosilicon to form a silicon-carbon negative electrode material. The material forms a porous carbon matrix through high temperature pyrolysis of zinc gluconate, providing buffer zones and conductive paths, improving the mechanical stability and electrical conductivity of the electrodes.
It significantly improves the cycle stability and reversible capacity of lithium-ion batteries, extends the cycle life of the battery, and increases the energy density, solving the problem of volume expansion of silicon negative electrode materials during charging and discharging.
Smart Images

Figure CN119650616A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a silicon-carbon negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the increasing global attention to sustainable energy and green travel, the demand for new energy vehicles and renewable energy storage technology is growing, which has prompted the rapid development of battery technology, especially lithium-ion battery technology. In lithium-ion batteries, the anode material is one of the key factors that determine battery performance. Silicon-based anode materials have attracted much attention due to their theoretical specific capacity of up to 4200mAh / g, which is much higher than the theoretical specific capacity of traditional graphite anodes (about 372mAh / g). However, the silicon anode expands significantly in volume during the battery charging and discharging process, resulting in poor cycle stability, which is the main obstacle to its commercial application.
[0003] The advantages of silicon anodes are their high energy density and low production cost, which makes them ideal for improving the performance of lithium batteries. However, silicon undergoes a huge volume change during the charge and discharge process (up to 300% or more), which leads to the cracking of electrode materials and the degradation of battery performance. In addition, the first coulombic efficiency of silicon anodes is usually low, and the capacity decays rapidly during the cycle.
[0004] In order to overcome these shortcomings of silicon negative electrodes, porous carbon matrix is currently used as a supporting material. The advantages of porous carbon matrix are its high specific surface area, good conductivity and mechanical strength, which can effectively buffer the volume expansion of silicon during charging and discharging, thereby improving the cycle stability of the battery. In addition, the porous carbon structure provides more anchoring points for silicon particles, which helps to maintain the integrity of the electrode structure.
[0005] Vapor deposition (CVD) technology is widely used to deposit silicon on porous carbon substrates because it can accurately control the thickness and uniformity of the silicon layer. The advantages of CVD technology are short production process, less equipment, low theoretical cost, and the ability to produce silicon-carbon composite materials with excellent charge and discharge efficiency and cycle stability.
[0006] Conductive polymer coating technology is also used to improve the performance of silicon negative electrodes. Conductive polymers such as polyaniline (PANI), polypyrrole (PPy) and polythiophene (PTh) can not only improve the conductivity of the electrode, but also act as a buffer layer to alleviate the volume change of silicon particles during charging and discharging. The advantage of conductive polymer coating is its good elasticity and adhesion, which helps to improve the mechanical stability and electrochemical performance of the electrode. Summary of the invention
[0007] Based on the technical problems existing in the background technology, the present invention proposes a silicon-carbon negative electrode material and a preparation method thereof and a lithium-ion battery. The silicon-carbon negative electrode material has a high specific surface area, excellent conductivity and stable cycle performance. When used in lithium-ion batteries, it exhibits excellent cycle stability and high reversible capacity during the charge and discharge process, effectively improving the energy density and cycle life of the lithium-ion battery, and providing a new technical approach for the preparation of silicon negative electrode materials for lithium-ion batteries, which has broad application prospects.
[0008] The present invention provides a silicon-carbon negative electrode material, comprising a porous carbon matrix, nano-silicon deposited on the surface and in the pores of the porous carbon matrix, and a conductive polymer layer coated on the surface of the nano-silicon;
[0009] The porous carbon matrix is formed by using zinc gluconate as a carbon source through high-temperature pyrolysis and carbonization.
[0010] In the present invention, zinc gluconate is used as a carbon source and is pyrolyzed and carbonized at high temperature to form porous carbon as a matrix, which can provide a "buffer" for silicon particles and can absorb the volume change of silicon, thereby reducing mechanical stress and preventing material rupture; the conductive polymer layer can provide a good electronic conduction path, improve the conductivity of the entire electrode, and the conductive polymer layer can also effectively connect the silicon particles, promote the rapid transmission of electrons in the electrode, and improve the overall performance of the electrode.
[0011] Preferably, the specific surface area of the porous carbon matrix is 1500-2200 m 2 / g, pore size 0.5-4nm;
[0012] Preferably, the particle size of the porous carbon matrix is 4-10 μm.
[0013] Preferably, the conductive polymer layer is formed by in-situ forming a conductive polymer on the surface of nano-silicon and then subjecting it to low-temperature pyrolysis and carbonization;
[0014] Preferably, the conductive polymer is at least one of polyaniline, polypyrrole or polythiophene.
[0015] The present invention also provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0016] S1, placing zinc gluconate in an inert gas for high-temperature pyrolysis and carbonization to obtain a porous carbon matrix;
[0017] S2, placing the porous carbon in a silicon source gas for chemical vapor deposition to obtain a silicon-carbon core;
[0018] S3, reacting the silicon-carbon core and the conductive polymer monomer in situ to form a conductive polymer, and then performing low-temperature pyrolysis and carbonization to obtain the silicon-carbon negative electrode material.
[0019] In the present invention, a porous carbon matrix is formed by zinc gluconate, and nano silicon particles are deposited on the porous carbon matrix. Then, by controlling the reaction conditions, a conductive polymer is polymerized on the surface of the silicon particles. The obtained silicon-carbon negative electrode material has a high specific surface area, excellent conductivity and stable cycle performance.
[0020] Preferably, in step S1, the inert gas is at least one of nitrogen, argon or helium;
[0021] Preferably, the temperature of the high temperature pyrolysis carbonization is 1100-1500° C., and the time is 1-3 hours.
[0022] Preferably, in step S2, the silicon source gas is at least one of monosilane, disilane, trichlorosilane or dichlorosilane;
[0023] Preferably, the chemical vapor deposition temperature is 700-900°C and the time is 4-6h;
[0024] Preferably, the silicon source gas further comprises an inert gas, and the volume proportion of the inert gas is 5-10%.
[0025] Preferably, in step S3, the conductive polymer monomer is at least one of an aniline monomer, a pyrrole monomer, a thiophene monomer or a 4-ethylenedioxythiophene monomer;
[0026] Preferably, the temperature of the low-temperature pyrolysis carbonization is 700-900° C. and the time is 4-6 hours.
[0027] Preferably, in step S3, before reacting the silicon-carbon core and the conductive polymer monomer in situ to form the conductive polymer, the surface of the silicon-carbon core is further modified by isocyanate;
[0028] Preferably, the isocyanate modification is achieved by coupling the silicon-carbon core with an isocyanate-containing silane coupling agent;
[0029] Preferably, the isocyanate-containing silane coupling agent is 3-isocyanatepropyltriethoxysilane.
[0030] In the present invention, the surface of the silicon-carbon core is modified by isocyanate, so that the surface of the silicon-carbon core is grafted with isocyanate groups, which can react with conductive polymer monomers, such as aniline monomers, pyrrole monomers, thiophene monomers or 4-ethylenedioxythiophene monomers, so that the resulting conductive polymer can be tightly combined with the surface of the silicon-carbon core, and a highly compatible interface layer is formed between the two, which is not only conducive to load transfer, but also can alleviate stress concentration. In the post-low-temperature pyrolysis and carbonization, the silicon / conductive polymer layer is pyrolyzed, and the conductive polymer converts the conductive polymer coated on the silicon surface into a soft carbon coating layer, which is tightly coated on the surface of nano-silicon. While further solving the silicon expansion, it is beneficial to improve the conductivity of the silicon-carbon negative electrode material and maintain the structural integrity of the silicon-carbon negative electrode material during the charge and discharge process, thereby increasing the cycle stability and rate performance of the lithium-ion battery.
[0031] The present invention also provides a lithium-ion battery, which includes the above silicon-carbon negative electrode material or the silicon-carbon negative electrode material prepared by the above preparation method.
[0032] Beneficial effects of the present invention:
[0033] In the present invention, firstly, zinc gluconate is thermally decomposed in a high temperature environment to form a porous carbon matrix in one step. The mechanism is that zinc oxide is first precipitated at high temperature, and then zinc oxide reacts with the carbon matrix, zinc is reduced to steam and carbon is oxidized to generate carbon monoxide. This process forms a porous structure in the carbon matrix. This porous carbon matrix is crucial to improving the performance of electrode materials due to its high specific surface area and abundant active sites, and can enhance contact with the electrolyte and improve the overall performance of the battery.
[0034] Furthermore, depositing silicon in a porous carbon matrix can reduce electrode breakage and material pulverization caused by volume changes of silicon, provide a support structure for silicon, help maintain the stability of the electrode structure, and maintain good structural integrity even after multiple charge and discharge cycles; the porous structure provides a large surface area and active sites, which helps to increase the contact area between silicon and the electrolyte and improve the storage and release efficiency of lithium ions.
[0035] Finally, conductive polymers are formed on the surface of the silicon / porous carbon matrix by in situ polymerization and converted into soft carbon during pyrolysis, which not only provides an additional conductive network but also helps to improve the electrochemical performance of the electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a SEM image of the silicon-carbon negative electrode material described in Example 1 of the present invention;
[0037] Figure 2 This is a cycle performance diagram of the silicon-carbon negative electrode material described in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0039] Example 1
[0040] This embodiment provides a silicon-carbon negative electrode material, including a porous carbon matrix, nano-silicon deposited on the surface and in the pores of the porous carbon matrix, and a conductive polymer layer coated on the surface of the nano-silicon.
[0041] The preparation method of the above silicon-carbon negative electrode material specifically includes:
[0042] (1) adding 10 g of high-purity zinc gluconate to 100 mL of deionized water, stirring the mixture at a rate of 500 r / min for 30 min using a magnetic stirrer to uniformly disperse the mixture, and vacuum drying the resulting solution at 80° C. for 4 h to remove the solvent to obtain a solid precursor; placing the solid precursor in a tubular furnace, heating the mixture to 1200° C. at a rate of 10° C. / min under an argon atmosphere, and maintaining the temperature for 2 h to complete pyrolysis to obtain a porous carbon matrix;
[0043] (2) placing the porous carbon substrate on a sample stage of a CVD system, introducing a mixed gas of monosilane and argon in a volume ratio of 10:1, and depositing at 800° C. for 5 h to form nanosilicon on the surface and in the pores of the porous carbon substrate to obtain a silicon-carbon core;
[0044] (3) The silicon-carbon core is added to 100 mL of a 0.5 mol / L hydrochloric acid solution and stirred to disperse evenly, then 3 g of aniline monomer is added and stirred to disperse evenly, and then 10 mL of a 2 mol / L ammonium persulfate aqueous solution is added dropwise, and the polymerization reaction is carried out at a rate of 50 r / min and at 5°C for 12 hours, followed by centrifugation, and the mixture is rinsed with an ethanol aqueous solution until neutral. After drying, the mixture is placed in a tubular furnace, and the temperature is increased to 800°C at a rate of 10°C / min under an argon atmosphere. After being kept warm for 5 hours, the silicon-carbon negative electrode material is obtained.
[0045] The silicon-carbon negative electrode material obtained in this example was scanned by electron microscope. The results are as follows: Figure 1 As shown, refer to Figure 1 It can be seen that the particle size of the silicon-carbon negative electrode material is about 5-8 μm. The micron-sized particles have better stress buffering, improve cycle stability, effectively improve initial coulomb efficiency, reduce electrolyte loss, and increase the overall life of the battery.
[0046] Example 2
[0047] This embodiment provides a silicon-carbon negative electrode material, including a porous carbon matrix, nano-silicon deposited on the surface and in the pores of the porous carbon matrix, and a conductive polymer layer coated on the surface of the nano-silicon.
[0048] The preparation method of the above silicon-carbon negative electrode material specifically includes:
[0049] (1) adding 10 g of high-purity zinc gluconate to 100 mL of deionized water, stirring the mixture at a rate of 500 r / min for 30 min using a magnetic stirrer to uniformly disperse the mixture, and vacuum drying the resulting solution at 80° C. for 4 h to remove the solvent to obtain a solid precursor; placing the solid precursor in a tubular furnace, heating the mixture to 1100° C. at a rate of 10° C. / min under an argon atmosphere, and maintaining the temperature for 3 h to complete pyrolysis to obtain a porous carbon matrix;
[0050] (2) placing the porous carbon substrate on a sample stage of a CVD system, introducing a mixed gas of disilane and argon in a volume ratio of 9:1, and depositing at 700° C. for 6 h to form nanosilicon on the surface and in the pores of the porous carbon substrate to obtain a silicon-carbon core;
[0051] (3) The silicon-carbon core is added to 100 mL of a 0.5 mol / L hydrochloric acid solution and stirred to disperse evenly, then 3 g of a pyrrole monomer is added and stirred to disperse evenly, and then 10 mL of a 2 mol / L potassium persulfate aqueous solution is added dropwise, and the polymerization reaction is carried out at a rate of 100 r / min and at 15°C for 6 hours, followed by centrifugation, and the mixture is rinsed with an ethanol aqueous solution until neutral. After drying, the mixture is placed in a tubular furnace, and the temperature is increased to 900°C at a rate of 10°C / min under an argon atmosphere. After being kept warm for 4 hours, the silicon-carbon negative electrode material is obtained.
[0052] Example 3
[0053] This embodiment provides a silicon-carbon negative electrode material, including a porous carbon matrix, nano-silicon deposited on the surface and in the pores of the porous carbon matrix, and a conductive polymer layer coated on the surface of the nano-silicon.
[0054] The preparation method of the above silicon-carbon negative electrode material specifically includes:
[0055] (1) adding 10 g of high-purity zinc gluconate to 100 mL of deionized water, stirring the mixture at a rate of 500 r / min for 30 min using a magnetic stirrer to uniformly disperse the mixture, and vacuum drying the resulting solution at 80° C. for 4 h to remove the solvent to obtain a solid precursor; placing the solid precursor in a tubular furnace, heating the mixture to 1500° C. at a rate of 10° C. / min under an argon atmosphere, and maintaining the temperature for 1 h to complete pyrolysis to obtain a porous carbon matrix;
[0056] (2) placing the porous carbon substrate on a sample stage of a CVD system, introducing a mixed gas of monosilane and argon in a volume ratio of 19:1, and depositing at 900° C. for 4 h to form nanosilicon on the surface and in the pores of the porous carbon substrate to obtain a silicon-carbon core;
[0057] (3) The silicon-carbon core is added to 100 mL of a 0.5 mol / L hydrochloric acid solution and stirred to disperse evenly, then 3 g of a thiophene monomer is added and stirred to disperse evenly, and then 10 mL of a 2 mol / L hydrogen peroxide aqueous solution is added dropwise, and the polymerization reaction is carried out at a rate of 80 r / min and at 10°C for 10 hours, followed by centrifugation, and the mixture is rinsed with an ethanol aqueous solution until neutral. After drying, the mixture is placed in a tubular furnace, and the temperature is increased to 700°C at a rate of 10°C / min under an argon atmosphere. After being kept warm for 4 hours, the silicon-carbon negative electrode material is obtained.
[0058] Example 4
[0059] This embodiment provides a silicon-carbon negative electrode material, including a porous carbon matrix, nano-silicon deposited on the surface and in the pores of the porous carbon matrix, and a conductive polymer layer coated on the surface of the nano-silicon.
[0060] The preparation method of the above silicon-carbon negative electrode material specifically includes:
[0061] (1) adding 10 g of high-purity zinc gluconate to 100 mL of deionized water, stirring the mixture at a rate of 500 r / min for 30 min using a magnetic stirrer to uniformly disperse the mixture, and vacuum drying the resulting solution at 80° C. for 4 h to remove the solvent, thereby obtaining a solid precursor; placing the solid precursor in a tubular furnace, heating the mixture to 1300° C. at a rate of 10° C. / min under an argon atmosphere, and maintaining the temperature for 2 h to complete pyrolysis, thereby obtaining a porous carbon matrix;
[0062] (2) placing the porous carbon substrate on a sample stage of a CVD system, introducing a mixed gas of monosilane and argon in a volume ratio of 10:1, and depositing at 800° C. for 5 h to form nanosilicon on the surface and in the pores of the porous carbon substrate to obtain a silicon-carbon core;
[0063] (3) The silicon-carbon core is added to 100 mL of a 0.5 mol / L hydrochloric acid solution and stirred to disperse evenly, then 3 g of aniline monomer is added and stirred to disperse evenly, and then 10 mL of a 2 mol / L ammonium persulfate aqueous solution is added dropwise, and the polymerization reaction is carried out at a rate of 50 r / min and at 5°C for 12 hours, followed by centrifugation, and the mixture is rinsed with an ethanol aqueous solution until neutral. After drying, the mixture is placed in a tubular furnace, and the temperature is increased to 800°C at a rate of 10°C / min under an argon atmosphere. After being kept warm for 5 hours, the silicon-carbon negative electrode material is obtained.
[0064] Example 5
[0065] This embodiment provides a silicon-carbon negative electrode material, including a porous carbon matrix, nano-silicon deposited on the surface and in the pores of the porous carbon matrix, and a conductive polymer layer coated on the surface of the nano-silicon.
[0066] The preparation method of the above silicon-carbon negative electrode material specifically includes:
[0067] (1) adding 10 g of high-purity zinc gluconate to 100 mL of deionized water, stirring the mixture at a rate of 500 r / min for 30 min using a magnetic stirrer to uniformly disperse the mixture, and vacuum drying the resulting solution at 80° C. for 4 h to remove the solvent to obtain a solid precursor; placing the solid precursor in a tubular furnace, heating the mixture to 1200° C. at a rate of 10° C. / min under an argon atmosphere, and maintaining the temperature for 2 h to complete pyrolysis to obtain a porous carbon matrix;
[0068] (2) placing the porous carbon substrate on a sample stage of a CVD system, introducing a mixed gas of monosilane and argon in a volume ratio of 10:1, and depositing at 800° C. for 5 h to form nanosilicon on the surface and in the pores of the porous carbon substrate to obtain a silicon-carbon core;
[0069] (3) adding the silicon-carbon core to 100 mL of ethanol-water solution with a volume ratio of 4:1, adding 5 mL of ammonia water and stirring to mix evenly, then adding 0.5 g of 3-isocyanatepropyltriethoxysilane, stirring and reacting at 60° C. for 6 h, centrifuging, washing with ethanol-water solution until neutral, and drying to obtain an isocyanate-modified silicon-carbon core;
[0070] (4) The above-mentioned isocyanate-modified silicon-carbon core was added to 100 mL of a 0.5 mol / L hydrochloric acid solution and stirred to disperse evenly, then 3 g of aniline monomer was added and stirred to disperse evenly, and then 10 mL of a 2 mol / L ammonium persulfate aqueous solution was added dropwise, and the polymerization reaction was carried out at a rate of 50 r / min and at 5°C for 12 hours, followed by centrifugation, and rinsed with an ethanol aqueous solution until neutral. After drying, the mixture was placed in a tubular furnace, and the temperature was increased to 800°C at a rate of 10°C / min under an argon atmosphere. After being kept warm for 5 hours, the silicon-carbon negative electrode material was obtained.
[0071] Comparative Example 1
[0072] This comparative example proposes a silicon-carbon negative electrode material, comprising a porous carbon matrix, nano-silicon deposited on the surface and in the pores of the porous carbon matrix, and a conductive polymer layer coated on the surface of the nano-silicon.
[0073] The preparation method of the above silicon-carbon negative electrode material specifically includes:
[0074] (1) adding 10 g of high-purity glucose to 100 mL of deionized water, stirring the mixture at 500 r / min for 30 min using a magnetic stirrer to disperse the mixture evenly, and vacuum drying the resulting solution at 80° C. for 4 h to remove the solvent to obtain a solid precursor; placing the solid precursor in a tubular furnace, heating the mixture to 1200° C. at a rate of 10° C. / min under an argon atmosphere, and maintaining the temperature for 2 h to complete pyrolysis to obtain a porous carbon matrix;
[0075] (2) placing the porous carbon substrate on a sample stage of a CVD system, introducing a mixed gas of monosilane and argon in a volume ratio of 10:1, and depositing at 800° C. for 5 h to form nanosilicon on the surface and in the pores of the porous carbon substrate to obtain a silicon-carbon core;
[0076] (3) The silicon-carbon core is added to 100 mL of a 0.5 mol / L hydrochloric acid solution and stirred to disperse evenly, then 3 g of aniline monomer is added and stirred to disperse evenly, and then 10 mL of a 2 mol / L ammonium persulfate aqueous solution is added dropwise, and the polymerization reaction is carried out at a rate of 50 r / min and at 5°C for 12 hours, followed by centrifugation, and the mixture is rinsed with an ethanol aqueous solution until neutral. After drying, the mixture is placed in a tubular furnace, and the temperature is increased to 800°C at a rate of 10°C / min under an argon atmosphere. After being kept warm for 5 hours, the silicon-carbon negative electrode material is obtained.
[0077] Comparative Example 2
[0078] This comparative example proposes a silicon-carbon negative electrode material, comprising a porous carbon matrix and nano-silicon deposited on the surface and in the pores of the porous carbon matrix.
[0079] The preparation method of the above silicon-carbon negative electrode material specifically includes:
[0080] (1) 10 g of high-purity zinc gluconate was added to 100 mL of deionized water, and stirred at a rate of 500 r / min for 30 min using a magnetic stirrer to make it evenly dispersed. The resulting solution was vacuum dried at 80° C. for 4 h to remove the solvent to obtain a solid precursor; the solid precursor was placed in a tubular furnace, and the temperature was raised to 1200° C. at a rate of 10° C. / min under an argon atmosphere. After being kept warm for 2 h, pyrolysis was completed to obtain a porous carbon matrix with a specific surface area of 1860 m 2 / g, pore size 0.5-4nm;
[0081] (2) The porous carbon substrate is placed on the sample stage of a CVD system, and a mixed gas of monosilane and argon with a volume ratio of 10:1 is introduced. After deposition at 800° C. for 5 hours, nano-silicon is formed on the surface and in the pores of the porous carbon substrate, thereby obtaining the silicon-carbon negative electrode material.
[0082] The silicon-carbon negative electrode material obtained in the embodiment and the comparative example was respectively mixed with conductive carbon black and a binder sodium alginate in a mass ratio of 8:1:1 and water was added to form a slurry, and the slurry was evenly coated on a copper foil. After drying, the slurry was placed in a vacuum drying oven at 70°C for 12 hours to form a negative electrode sheet. A 1 mol / L LiPF6 solution (the solvent is ethylene carbonate EC / diethyl carbonate DEC / ethyl methyl carbonate EMC, v / v / v=1:1:1) was used as the electrolyte, a metal lithium sheet was used as the positive electrode, and a Cellgard2400 polypropylene porous membrane was used as the diaphragm, and the batteries were assembled into a lithium-ion battery in a deoxygenated and dehydrated glove box filled with argon.
[0083] The button cell was placed on a LAND battery tester for electrochemical performance testing, with a charge and discharge voltage range of 0.01-1.5V and a charge and discharge current of 0.5C. The test results are listed in Table 1.
[0084] Table 1 Electrochemical test results of silicon-carbon negative electrode materials obtained in Examples and Comparative Examples
[0085]
[0086] Figure 2 The cycle performance diagram of the silicon-carbon negative electrode material described in Example 1, refer to Table 2 and Figure 1 It can be seen that the discharge specific capacity of the negative electrode sheet corresponding to the silicon-carbon negative electrode material described in Example 1 can reach 897 mAh / g, the first efficiency is 88.0%, and after 420 cycles, it can still maintain 53.4% of the capacity; it can be seen that the negative electrode material of the present invention exhibits good electrochemical properties because nano-silicon is deposited in porous carbon, which effectively inhibits volume expansion, and the outer layer is a conductive polymer, which effectively improves conductivity, is beneficial to the transmission of electrons, increases reaction active sites, and further buffers volume expansion.
[0087] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A silicon-carbon negative electrode material, characterized in that: It includes a porous carbon matrix, nano-silicon deposited on the surface and in the pores of the porous carbon matrix, and a conductive polymer layer coated on the surface of the nano-silicon; The porous carbon matrix is formed by using zinc gluconate as a carbon source through high-temperature pyrolysis and carbonization.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The specific surface area of the porous carbon matrix is 1500-2200m 2 / g, pore size 0.5-4nm; Preferably, the particle size of the porous carbon matrix is 4-10 μm.
3. The silicon-carbon negative electrode material according to claim 1 or 2, characterized in that: The conductive polymer layer is formed by in-situ forming a conductive polymer on the surface of nano-silicon and then subjecting it to low-temperature pyrolysis and carbonization; Preferably, the conductive polymer is at least one of polyaniline, polypyrrole or polythiophene.
4. A method for preparing a silicon-carbon negative electrode material, characterized in that: The steps include: S1, placing zinc gluconate in an inert gas for high-temperature pyrolysis and carbonization to obtain a porous carbon matrix; S2, placing the porous carbon in a silicon source gas for chemical vapor deposition to obtain a silicon-carbon core; S3, reacting the silicon-carbon core and the conductive polymer monomer in situ to form a conductive polymer, and then performing low-temperature pyrolysis and carbonization to obtain the silicon-carbon negative electrode material.
5. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step S1, the inert gas is at least one of nitrogen, argon or helium; Preferably, the temperature of the high temperature pyrolysis carbonization is 1100-1500° C., and the time is 1-3 hours.
6. The method for preparing the silicon-carbon negative electrode material according to claim 4 or 5, characterized in that: In step S2, the silicon source gas is at least one of monosilane, disilane, trichlorosilane or dichlorosilane; Preferably, the chemical vapor deposition temperature is 700-900°C and the time is 4-6h; Preferably, the silicon source gas further comprises an inert gas, and the volume proportion of the inert gas is 5-10%.
7. The method for preparing the silicon-carbon negative electrode material according to any one of claims 4 to 6, characterized in that: In step S3, the conductive polymer monomer is at least one of an aniline monomer, a pyrrole monomer, a thiophene monomer, or a 4-ethylenedioxythiophene monomer; Preferably, the temperature of the low-temperature pyrolysis carbonization is 700-900° C. and the time is 4-6 hours.
8. The method for preparing the silicon-carbon negative electrode material according to any one of claims 4 to 7, characterized in that: In step S3, before the silicon-carbon core and the conductive polymer monomer are reacted in situ to form the conductive polymer, the surface of the silicon-carbon core is modified by isocyanate; Preferably, the isocyanate modification is achieved by coupling the silicon-carbon core with an isocyanate-containing silane coupling agent; Preferably, the isocyanate-containing silane coupling agent is 3-isocyanatepropyltriethoxysilane.
9. A negative electrode of a lithium ion battery, characterized in that: It includes the silicon-carbon negative electrode material according to any one of claims 1 to 3 or the silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 4 to 8.
10. A lithium ion battery, characterized in that: Comprising the negative electrode as claimed in claim 9.
Citation Information
Cited By
Silicon-carbon composite material as well as preparation method and application thereof
CN120637442A
Silicon-carbon active material, preparation method and application thereof, and lithium ion battery
CN120895617A
A silicon-carbon active material, its preparation method and application in lithium-ion batteries
CN120895617B
Bio-based silicon-carbon negative electrode porous carbon material, preparation method and application of bio-based silicon-carbon negative electrode porous carbon material
CN120964804A